Development of Interactive Learning Video of Islamic Integrated Mathematics to Improve Mathematical Critical Thinking Abilities of Grade VIII Students of SMP Ma'arif NU Paguyangan - Tomi Rahmatulloh Firdaus; Nidaul Hana (Faculty of Tarbiya and Teacher Trainning, Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri Purwokerto, 2026)
Critical thinking skills have become one of the essential competencies that students must possess in the era of rapidly advancing technology. In the midst of an overwhelming flow of information, students can no longer passively accept information at face value they must be able to critically filter and analyze it wisely. Unfortunately, at SMP Ma'arif NU Paguyangan, students' mathematical critical thinking skills remain relatively low. This is mainly due to the continued reliance on conventional lecture methods and the use of textbooks as the primary learning resource. Starting from this problem, this study aims to develop a mathematics learning medium in the form of an interactive video that integrates Islamic values. This media is designed to be valid and effective in enhancing the critical thinking skills of eighth-grade students. The study uses the Research and Development (R&D) method with a quasi-experimental approach to test the effectiveness of the developed product. The results of the study indicate that the developed learning video is declared valid and feasible for use. Validation by subject matter experts yielded a score of 80%, media experts 81.42%. Additionally, the video has proven to be effective in improving students' critical thinking skills, as evidenced by the average N-Gain score of the experimental class reaching 0.8 (categorized as “high”), significantly better than the control class, which only achieved 0.43 (categorized as “medium”). Data analysis using an independent two-sample t-test resulted in a significance value of 0.000, which is far below the 0.05 threshold. This means the null hypothesis (H₀) is rejected, and the alternative hypothesis (H₁) is accepted. Therefore, it can be concluded that the developed interactive mathematics learning video, in addition to being validated by experts and teachers, has also been proven effective in improving the critical thinking skills of eighth-grade students at SMP Ma'arif NU Paguyangan